PENGARUH KEPUASAN KERJA, ORGANIZATIONAL CITIZENSHIP BEHAVIOR DAN BEBAN KERJA TERHADAP TURNOVER INTENTION : Karyawan Generasi Z Yang Berdomisili Di Rw 05, Kelurahan Kuningan Barat, Kecamatan Mampang Prapatan - Emi Hidayah (2022)
This study aims to determine whether there is an influence between job satisfaction, organizational citizenship behavior, and workload on the turnover intention of generation z employees who live in RW 05, Kuningan Barat Village, Mampang Prapatan District. This study is a quantitative study with a sample of 45 employees of Generation Z who live in RW 05, Kuningan Barat Village, Mampang Prapatan District. The sampling technique used was saturated sampling technique. analysis technique uses descriptive analysis and inferential analysis with the help of SmartPLS 3.0. Hypothesis testing obtains that job satisfaction has a positive and significant effect on turnover intention of generation z employees RW 05, organizational citizenship behavior has a positive and insignificant effect on turnover intention of generation z employees RW 05, workload has a positive and insignificant effect on turnover intention of generation z employees RW 05, and the variables of job satisfaction, organizational citizenship behavior, and workload simultaneously affect turnover intention in Generation Z employees RW 05. Keywords: Job Satisfaction, Organizational Citizenship Behavior, Workload, and Turnover Intention.